Predictors of Inappropriate Antibiotic Prescribing in Australian General Practice / Primary Care Settings - Harrison, Amy Elizabeth (Curtin University, 2023)
The objective of this thesis was to identify Guideline non-conforming prescribing of systemic antibiotics in Western Australian general practice for initial presentations of acute upper respiratory tract infection and urinary tract infection. Using quantitative methods, large-scale, longitudinal datasets were utilised to ascertain predictors of inappropriate prescribing, and to determine trends in inappropriate antibiotic prescribing over time. Significant inappropriate prescribing was detected and multiple predictors of inappropriate prescribing were identified, which can assist with antibiotic stewardship.